1281 Mirnas in extracellular vesiclesmediate the effect of particulate matter exposure on coagulation in a large sample of overweight/obese adults. (24th April 2018) - Bollati, V; Carugno, M; Pergoli, L; Cantone, L; Iodice, S; Favero, C; Hoxha, M; Dioni, L; Vigna, L; Bonzini, M; Pesatori, AC
Abstract : Introduction: In Italy about 45% of people aged ≥18 years are overweight/obese and might thus be more susceptible to the adverse health effects of air pollution exposure. Particulate matter ≤10 µm (PM10) represents a common pollutant of living and working environments and has been associated with increased risk of cardiovascular diseases (CVD) and hypercoagulability. Extracellular vesicles (EV) might play an important role in PM-related CVD, as they can travel in body fluids and transfer miRNAs between cells. We investigated whether PM10 exposure is associated with changes in fibrinogen levels, EV release, and EV-miRNA content in a large sample of overweight/obese adults. Methods: EV concentrations were quantified by nanoparticle tracking analysis and flow cytometry. To identify altered levels of EV-miRNAs, we profiled miRNAs of 883 subjects by the QuantStudio 12K Flex Real Time PCR System. The top 40 EV-miRNAs were validated through custom miRNA plates. Statistical analyses included multiple linear regressions, mediation analysis and bioinformatics analysis. Results: In a sample of 1630 overweight/obese subjects from the SPHERE (S usceptibility to P article H ealth E ffects, miR NAs and E xosomes) study, short-term exposure to PM10 was associated with increased release of EVs, especially those from monocyte/macrophage components (CD14+) and platelets (CD61+). Nine EV-miRNAs (let-7c-5p; miR-106a-5p; miR-143–3 p; miR-185–5 p; miR-218–5 p; miR-331–3 p; miR-642–5 p; miR-652–3 p; miR-99b-5p) were downregulated in response to PM10 exposure and exhibited putative roles in CVD. Five of these nine EV-miRNAs were mediators in the positive association between PM10 exposure and fibrinogen levels. Conclusions: Our study sheds some light on the potential mechanisms underlying the adverse cardiovascular health effects of air pollution exposure. Our results were obtained in a hypersusceptible population and thus strengthen the relevance of health promotion interventions for both the general public and the working population, as they might be particularly feasible in the workplace.